Analisis Kinerja Guru berdasarkan Konflik, Beban dan Stres Kerja (Studi pada SMP Negeri di Kecamatan Bandar Dua Pidie Jaya) - Nazaruddin, Nazaruddin; Kamaruddin, Kamaruddin; Luthfi, Luthfi (peusangan, 2024)
Teacher performance issues are always interesting to study. Because this is still a problem in several regional schools, such as junior high schools in Bandar Dua sub-district, Pidie Jaya. This study examines the factors of conflict, workload and work stress. The study was conducted on 110 state junior high school teachers in Bandar Dua sub-district using a quantitative-associative method. The results found that conflict, workload and work stress significantly influenced teacher performance. Each was 24,29 percent, 12,91 percent and 18,26 percent. 2) Simultaneously, work conflict, workload and work stress contributed significantly to teacher performance by 46.8 percent. And there is a causal relationship between the variables of conflict, workload and work stress.